Radiation Generator Design for Increasing Efficiency in Gas Stove - M. Djamil (Natural B, Journal of Health and Environmental Sciences, 2012)
It has been designed an additional part of  a gas stove called ARP that is aimed to increase an efficiency of  the stove.  The ARP was made of Nickel that was a circle in shaped. The ARP was varied in  diameter of the phrame, a length of wire, and a diameter of wire named Shape Factor (FB). An other variables set up to add an efficiency of stove was position factor (FP) consisting of a position of the ARP in between the stove and the load.  The effisiency of stove was investigated by varying the FB and FP factors in a different set of value. The results showed that the efficiency of  stove was increased of  20 % for the FP was set of 0.17 and the FB was varied between 0.31 and 0.42.